Searching for Religious Discrimination among Anganwadi Workers in India: An Experimental Investigation - Utteeyo Dasgupta; Subha Mani; Prakarsh Singh (Institute for the Study of Labor (IZA), 2016)
This paper examines whether, in India, discriminatory practices by government-employed child caregivers along religious lines, lead to differential health outcomes among the care receiving children. Child caregivers participate in a novel allocation game where we incorporate treatments to disentangle statistical and taste-based discrimination. Our findings find no evidence of taste-based discrimination or statistical discrimination among the child caregivers. We also weigh-in on the usefulness of non-incentivized experiments in discrimination experiments.
Keywords: C9; D3; I1; O1; 330; artefactual field experiment; discrimination; health; allocation game; India; religion